2019
DOI: 10.1585/pfr.14.3401112
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Study of Energetic Ion Driven Instabilities near the Lower Hybrid Resonance Frequency in a Plasma with Increasing Density

Abstract: Using a one-dimensional electromagnetic particle code which simulates self-consistently the full ion and electron dynamics, we study instabilities driven by energetic ions injected continuously in a plasma where the density and the lower-hybrid resonance frequency ω LH increase with time. The simulation shows that the ion cyclotron harmonic wave with ω lΩ i , where l is an integer and Ω i is the ion cyclotron frequency, is excited when ω LH becomes close to lΩ i. When ω LH is greater than lΩ i , this wave coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…In this letter, we perform 1D3V (one-dimensional, three-velocity components), electromagnetic, full PIC simulations, using the code which was used in Moritaka et al (2016) and now named PASTEL. PIC simulations are commonly used to study ion-ring instabilities that drive the LHWs (Min & Liu, 2015;Toida et al, 2019;Winske & Daughton, 2012. We use realistic parameters in the simulations based on the observation at 4,000 km altitude (Cattell et al, 2002), as shown in Table 1.…”
Section: Simulation Methods and Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…In this letter, we perform 1D3V (one-dimensional, three-velocity components), electromagnetic, full PIC simulations, using the code which was used in Moritaka et al (2016) and now named PASTEL. PIC simulations are commonly used to study ion-ring instabilities that drive the LHWs (Min & Liu, 2015;Toida et al, 2019;Winske & Daughton, 2012. We use realistic parameters in the simulations based on the observation at 4,000 km altitude (Cattell et al, 2002), as shown in Table 1.…”
Section: Simulation Methods and Parametersmentioning
confidence: 99%
“…Considering that energetic ions are continuously injected along the magnetic field in the polar region, it is reasonable that we use the energetic‐ion injection model in the simulations where energetic ions and the same number of electrons are continuously injected into the plasma. Some simulation studies (Kotani et al., 2021; Toida et al., 2019) have shown that the energetic‐ion injection plays a crucial role in the acceleration of background ions and the development of ion‐ring instabilities. The position and gyro‐phase of these particles are given at random.…”
Section: Simulation Methods and Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…This tends to confirm our identification of this particular subset of the fusion-born protons, near their birth energy, as a candidate energetic ion population responsible for the bursting ICE. An alternative scenario reported in [62] suggests that 178 keV NBI protons, injected tangentially with low pitch angle, could also excite ICE with a spectrum displaying a substantial frequency shift from integer cyclotron harmonics. This approach differs from the one explored in this paper, in that the free energy available to destabilise electromagnetic waves is much lower than for the 3.02 MeV fusion-born protons we consider here.…”
Section: Introductionmentioning
confidence: 99%
“…This approach differs from the one explored in this paper, in that the free energy available to destabilise electromagnetic waves is much lower than for the 3.02 MeV fusion-born protons we consider here. The lower velocities v ∥ together with higher k ∥ [62] result in k ∥ v ∥ being a small fraction of the proton cyclotron frequency Ω H when considering the resonant condition of the nth proton cyclotron harmonic including Doppler shift:…”
Section: Introductionmentioning
confidence: 99%